ANALISIS KECUKUPAN RUANG TERBUKA HIJAU (RTH) KOTA BATAM - Shirly Indriana Putri; Nurul Qomar; Yossi Oktorini (Jurnal Belantara, 2021)
Batam City is an industrial city and has a total area of 1,570.35 km2 with a land area of 715 km2. Following the economic development and increasing population, the green open space in Batam City is decreasing. The purpose of this research was to analyze the adequacy of Batam’s green open space based on the criteria of Law No. 26 of 2007 concerning Spatial Planning and Minister of Public Works Regulation No. 5 of 2008 concerning Guidelines and Utilization of Green Open Space. This research was conducted with a spatial analysis method based on land cover information from the interpretation of Landsat 8 OLI image recording on 05-06-2018. Based on the results showed that Batam’s green open space is still 221.400 ha or 32.05% from land area. It means, Batam City’s open space is still sufficient at least 30% according to Law No. 26 of 2007 and Minister of Public Works Regulation No. 5 of 2008. The largest type of land cover in green open space is secondary dry land forest, covering 79.200 ha (11.45%). Keyword : Batam City, analysis, green open space.